2014
DOI: 10.1007/s10765-014-1711-4
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Shear Viscosity of Low-Viscosity Liquids

Abstract: A thickness shear quartz resonator technique is described to measure the shear viscosity of low-viscosity liquids in the frequency range from 6 MHz to 130 MHz. Examples of shear-viscosity spectra in that frequency range are presented to show that various molecular processes are accompanied by shear-viscosity relaxation. Among these processes are conformational variations of alkyl chains, with relaxation times τ η of about 0.3 ns for n-pentadecane and n-hexadecane at 25 • C. These variations can be well represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…As seen in Figure , the normalized spectra appear to be bimodal, with the reduced relaxation frequencies of 2πη 0 ν ≈ 20 and 400 MPa. The bimodal viscoelastic relaxation of higher alcohols was suggested by the combination of the transverse and longitudinal ultrasonic spectroscopies, which was later confirmed by MD simulation . The presence of the bimodal relaxation has also been confirmed in a deeply supercooled region using conventional rheometers. …”
mentioning
confidence: 70%
“…As seen in Figure , the normalized spectra appear to be bimodal, with the reduced relaxation frequencies of 2πη 0 ν ≈ 20 and 400 MPa. The bimodal viscoelastic relaxation of higher alcohols was suggested by the combination of the transverse and longitudinal ultrasonic spectroscopies, which was later confirmed by MD simulation . The presence of the bimodal relaxation has also been confirmed in a deeply supercooled region using conventional rheometers. …”
mentioning
confidence: 70%
“…Viscoelastic spectra of liquid 1-alcohols are known to exhibit bimodal relaxation. Our recent molecular dynamics (MD) simulation study demonstrated, from the comparison between the viscoelastic spectra and the intermediate scattering function (ISF), that the slower relaxation mode can be assigned to the coupling with the mesoscopic dynamics, whereas the faster mode can be ascribed to microscopic structural relaxation . The picture obtained by the MD simulation was later confirmed experimentally on 3,7-dimethyl-1-octanol using γ-ray quasi­elastic scattering spectroscopy .…”
Section: Introductionmentioning
confidence: 78%
“…Viscoelastic relaxation is another target for the comparison with the dielectric relaxation spectrum. The frequency-dependent shear viscosity of n -alcohols can be measured at the ambient condition by means of transverse ultrasonic technique. , Because many monoalcohols are easily supercooled, a conventional mechanical rheometer can also be applied to the deeply supercooled state. Jakobsen and co-workers measured the dielectric and viscoelastic spectra of supercooled 2-ethyl-1-hexanol and 2-butanol at various temperatures near the glass transition and demonstrated that the time scale of the viscoelastic relaxation is close to that of the high-frequency dielectric process …”
Section: Introductionmentioning
confidence: 99%